2009
DOI: 10.1159/000218129
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Centromeres: Structural and Analytical Investigations with High Resolution Scanning Electron Microscopy in Combination with Focused Ion Beam Milling

Abstract: Whole mount mitotic metaphase chromosomes of different plants and animals were investigated with high resolution field emission scanning electron microscopy (FESEM) to study the ultrastructural organization of centromeres, including metacentric, acrocentric, telocentric, and holocentric chromosome variants. It could be shown that, in general, primary constrictions have distinctive ultrastructural features characterized by parallel matrix fibrils and fewer smaller chromomeres. Exposure of these structures depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…Thus identical centromeric sequences may be specifically recognized by protein complexes and/or specific centromeric chromatin may be differentially marked allowing subtypes clustering. Thus, specific epigenetic marks have been described in plant acrocentric chromosomes [45] but also in mammals with specific H3K9me3 marks on pericentromeric and centromeric chromatin and with the presence of non coding transcripts and histone variants (for a review see [46]). In vivo data also support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus identical centromeric sequences may be specifically recognized by protein complexes and/or specific centromeric chromatin may be differentially marked allowing subtypes clustering. Thus, specific epigenetic marks have been described in plant acrocentric chromosomes [45] but also in mammals with specific H3K9me3 marks on pericentromeric and centromeric chromatin and with the presence of non coding transcripts and histone variants (for a review see [46]). In vivo data also support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Using these data sets, 3D reconstructions with high resolution can be calculated, opening doors to analysis and quantification of structures that were inaccessible until now. This FIB/FESEM approach has been successfully applied in our lab for investigating chromosome architecture as a means to more precise chromatin analysis in mitotic chromosomes (Schroeder‐Reiter et al , 2009; Schroeder‐Reiter & Wanner, 2009; Heckmann et al , 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Functionally, the centromere is primarily responsible for ordered chromosome segregation by sister chromatid cohesion, kinetochore and spindle assembly and checkpoint regulation in mitosis and meiosis. Centromeres are structurally distinct from the chromosome arms, exhibiting exposed parallelly oriented chromatin fibers and fewer, smaller chromomeres than the chromosomes arms (Wanner & Formanek, 2000; Metcalfe et al , 2007; Schroeder‐Reiter & Wanner, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Centromeric ridges may be formed at highly compacted chromatin fibres and appear as 50 nm thick, globular structures , which is consistent with our own observations of denatured chromosomes. Such prominent rounded projections at the centromere [Jack et al, 1985] and the pericentromeric region of C-banded chromosomes have been observed by SEM [Jack et al, 1985;Schroeder-Reiter and Wanner, 2009] and AFM [Tan et al, 2001]. Interestingly, compaction in the pericentromeric region was affected to a lesser degree than along the chromosome arms [Jack et al, 1985].…”
Section: Discussionmentioning
confidence: 65%